Bangladesh : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Bangladesh highlights that economic growth in Bangladesh continues to be strong with stable inflation. Sustained growth in the ready-made garment sector with abundant low-cost labor has helped the economy to diversify away from the agricultural sector to a more manufacturing-based economy. Remittance inflows from Bangladeshis overseas continue to play an important role in promoting private consumption and external stability. While the economy still has significant potential with favorable demographics, to ensure sustainability and resilience of growth, the country needs to keep upgrading its macroeconomic policy framework and advance a range of structural measures. Bangladesh Bank should monitor inflation developments closely and stand ready to adjust its stance as needed. A gradual increase in exchange rate flexibility would help buffer the economy against external shocks and preserve the level of reserves. Continuous improvements in public financial management and frameworks to limit vulnerability to corruption will help the authorities' goal to reach upper middle-income country status.